Risk management in the design of the organization and technology for the construction and their implementation - Galinskyі O.; Emelianova, O.; Tytok, V. (Ways to Improve Construction Efficiency, 2021)
Risks are inevitable in any construction project. Risk management methodology is used to eliminate or mitigate their consequences in construction project management. Risk management involves the establishment of risk awareness, integration of basic principles of risk policy and organizational integration. This allows you to actively prepare the project for the inevitable problems and increase transparency. This is an ongoing process throughout the project life cycle, as the risks will be constantly changing. Risk management is the process of identifying, assessing and responding to risks, so it is important to work as an integrated project team from the first phases to identify risks and effectively deal with them when they arise. The benefits of the process are a clearer understanding of the specific risks associated with the project, supported by solutions through detailed analysis and accumulation of data that can be used to manage risks in the future. Ineffective implementation of risk management is often due to the lack of formalized procedures, lack of continuity in different phases of the project and inadequate integration of knowledge management and interaction between processes and parties. The article reveals the importance of identifying risks at the very first stage, which allows to reduce the problems during their detection. Attention is paid to risk analysis and risk management at all stages of the project. This is especially important when building in compacted buildings. A risk management plan is proposed, which provides timely identification and identification of potential problems and should be integrated into the project, from conceptual design to operation with extension to each stage. It should be based on principles such as risk identification, risk assessment, risk response and risk monitoring. The element of risk management algorithm is considered in more detail - identification of initial risks by creating and using a risk register, especially in the conditions of compacted construction.